Decoding Disciplinary Nuances: A Comparative Study of Move Structures, Verb Tense Patterns, and Lexical Density in Soft and Hard Science Abstracts - Rahman, M Arinal; Herlina, Silvia; Pernantah, Piki Setri; Nengsih, Yanti Karmila; Aini, Wirdatul (Universitas Negeri Padang, 2024)
Research article abstracts play a vital role in shaping initial impressions of scholarly work. This study investigates nuances in abstract writing across arts and humanities, social sciences, physics and astronomy, and chemistry. Using Bhatia's four-move and Hyland's five-move models, we analyze rhetorical move structures in 20 recent abstracts from top journals in each discipline. Verb tense preferences are examined through Tseng's approach, with a focus on the introduction move. Lexical density ratios are calculated following Halliday to assess complexity. Results reveal distinct move patterns between soft sciences (arts and humanities, social sciences) emphasizing logical flow, and hard sciences (physics and astronomy, chemistry) prioritizing conciseness. Verb tense analysis exposes tailored rhetorical strategies, with soft sciences exhibiting varied tenses and hard sciences consistently using present perfect tense to frame background. Lexical density is higher in soft science abstracts indicating more descriptive narratives, while hard science abstracts are more information-dense. These disciplinary nuances underscore the need for tailored guidelines and training in abstract writing. Findings contribute insights to enhance coherence, aligned with the conventions and epistemologies of diverse scientific communities.